(untitled) (Journal of Partial Differential Equations, 2004)
We consider the compactness theorem for the positive solutions of the equation Δu + h_1u^α + h_2u^β = 0 in Ω ⊂ R^n and obtain the measure estimate of the blow up set for positive smooth solutions u_i of the above equation with ||u_i||_H¹(Ω) + ||u_i||_L^α+1(Ω) + ||u_i||_L^β+1(Ω) bounded.